Optimisasi Faktor Beban melalui Metode Load Shifting untuk Menurunkan Biaya Tagihan Listrik - I Wayan Suriana; I Wayan Sugara Yasa; I Nyoman Gede Adrama; Agus Supranartha (Jurnal Ragam Pengabdian, 2026)
Nowadays, electrical energy is an essential necessity in modern life. To meet the demand for electricity in various sectors, such as households, industry, business, and tourism, it is necessary to improve the quality, quantity, and reliability of electricity supply. Efforts to improve electrical energy services require cooperation between PLN as a provider and the community as a user. One form of community contribution in supporting service improvement is by moving electricity use from peak load time (WBP) between 18.00-22.00 to outside peak load time (LWBP) at 22.00-18.00. This study aims to analyze the effect of load shifting on consumer load factors and its impact on electricity bill components, including energy costs, street lighting taxes, and stamp duty costs, on medium-voltage customers. Data was collected through a survey at PT PLN (Persero) Bali Medium Voltage Service Area Distribution (APTM) and interviews with 73 customers as a sample. The results of the study show that the shift in load from WBP to LWBP significantly increases PLN's efficiency by distributing electricity more evenly to consumers. This method also improves the load factor, which contributes to cost savings in generation and distribution of electricity as the plant does not need to operate at maximum capacity. One effective way to reduce the load on electricity is to move consumption from night to morning or day.